Data_Sheet_1_Multi-Tiered Culturally Responsive Behavior Support: A Qualitative Study of Trauma-Informed Education in an Australian Primary School.docx - Dayna Schimke; Govind Krishnamoorthy; Kay Ayre; Emily Berger; Bronwyn Rees (2022)
There is growing awareness of the impact of intergenerational trauma and community disadvantage on the educational achievement of Aboriginal and Torres Strait Islander (First Nations) children in Australia. Scholars have identified the need for culturally responsive and trauma-informed approaches to complement existing disciplinary and behavior support practices utilized in schools. This pilot research project explored the experiences of primary school teachers who were supported to implement trauma-informed practices in a regional primary school with a large number of First Nations students. Qualitative interviews with eight teachers were conducted after a 3-year (2017–2020) implementation of the Trauma-Informed Behavior Support (TIBS) program. Using a thematic analysis approach, the study identified the following themes: changes in teacher knowledge about the impact of intergenerational trauma, acknowledgment of the multi-systemic influences on student behavior difficulties, increased self-efficacy in providing culturally safe learning environments and strategies for building relationships with First Nations students. The findings offer insights into factors that support the successful and sustainable implementation of culturally responsive and trauma-informed practices in primary school settings.